The Use of Single Versus Multiple Doses Cefotaxime as a Prophylactic Antibiotic in Maxillofacial Fractures - Atalla Rejab; Mohmmed K Hassouni (University of Mosul, College of Dentistry, 2012)
Aim: The study aims to test the efficacy of using a single dose of cefotaxime antibiotic intravenously compared to the same drug when used for five days in the prevention of surgical site infection follow-ing maxillofacial fracture operations. Materials and Methods: The study group consisted of 78 pa-tients of different social and educational levels who have sustained maxillofacial fractures. All patients were planned to undergo operative procedures under general anesthesia to treat their fractures. Patients were randomized preoperatively into two groups ( Group A and Group B). Each patient in group A received a single dose of cefotaxime sodium (claforan) 40mg/kg body weight given intravenously at the induction of general anesthesia. No further dose of any antibiotic was given subsequently. Each patient in group B received cefotaxime sodium intravenously 20mg/kg twice daily for five days, start-ing the first dose of cefotaxime sodium at the induction of general anesthesia. During hospitalization postoperatively, patients were examined for signs and symptoms of surgical site infection. After dis-charge, the patients were recalled to the clinic for post-operative examination at 1, 2 , 3 and 4 weeks. Results: Only one patient out of 43 patients in the first group showed signs and symptoms of infection which was confirmed by culture and sensitivity test. Two cases of postoperative infection out of 35 patients developed infection in the second group. Conclusions: Using a single dose of cefotaxime was found to be comparable or even better than the use of the same drug for five days as a prophylactic antibiotic.